Gamma-delta T-cell large granular lymphocytic leukemia in the setting of rheumatologic diseases - Gorodetskiy, Vadim; Sidorova, Yulia; Biderman, Bella; Kupryshina, Natalia; Ryzhikova, Natalya; Sudarikov, Andrey (Frontiers in Cell and Developmental Biology, 2024)
Background: T-cell leukemia originating from large granular lymphocytes (T-LGL leukemia) is a rare lymphoid neoplasia characterized by clonal proliferation of large granular T lymphocytes expressing αβ or γδ T-cell receptor (TCR) on the cell membrane. γδT-LGL leukemia, accounting for approximately 17% of all T-LGL leukemia cases, is associated with autoimmune diseases.However, the features of γδT-LGL leukemia in patients with rheumatologic diseases are still insufficiently characterized.In this retrospective study, 15 patients with rheumatologic disease-associated γδT-LGL leukemia were included. The patients were obtained from a single center from 2008 to 2023. Data related to clinical characteristics and rheumatologic diagnoses were collected.TCR-δ gene rearrangements), and signal transducer and activator of transcription (STAT) 3 and STAT5B mutation analyses (by next-generation sequencing) were performed on blood, bone marrow, and spleen samples.Results: All but one patient had rheumatoid arthritis (RA). In 36% of patients, manifestations of γδT-LGL leukemia were present before or concurrently with clinical manifestations of RA.Splenomegaly was observed in 60% of patients and neutropenia (<1.5 × 10 9 /L) was detected in 93% of cases. CD4 -/CD8 -and CD4 -/CD8 + subtypes were detected in seven cases each.Mutations in STAT3 were detected in 80% of patients; however, STAT5B mutations were not detected. Evaluations of T-cell clonality and variant allele frequencies at STAT3 in the blood, bone marrow, and spleen tissue revealed an unusual variant of CD4 -/CD8 -γδT-LGL leukemia with predominant involvement of the spleen, involvement of the bone marrow to a less extent, and no tumor cells in peripheral blood.The mechanism by which γδT-LGL leukemia may induce the development of RA in some patients requires further investigation. Cases of RA-associated γδT-LGL leukemia with neutropenia and splenomegaly but no detectable tumor-associated lymphocytes in peripheral blood (the so-called splenic variant of T-LGL leukemia) are difficult to diagnose and may be misdiagnosed as Felty syndrome or hepatosplenic T-cell lymphoma.